Disability and Access to Social Services Among Women in Bugambi Subcounty, Sironko District - Manuel Mudambo (Uganda Christian University, 2024)
This study examined the impact of disability on access to social services among women in Bugambi Sub County, Sironko District. The research aimed to investigate how disability affected access to healthcare services, employment opportunities, and community support networks. A mixed-method approach was employed, utilizing questionnaires and interviews to collect data from women with disabilities, healthcare providers, employers, and community support organizations. Regression analysis was applied to assess the relationship between disability-related factors and access to social services. The analysis revealed a strong correlation (R = 0.683) and indicated that disability-related variables explained 46.7% of the variance (R² = 0.467) in access to these services. The findings showed that disability greatly influenced access to healthcare, with respondents highlighting the need for specialized training for providers and a reduction of societal stigma. Employment opportunities for women with severe disabilities were often limited, with education and financial support identified as critical factors in improving outcomes. Access to community support networks was found to be variable, underscoring the necessity for inclusive and tailored support mechanisms. These findings emphasized the importance of targeted interventions to address discrimination, enhance training, and improve infrastructure to better support women with disabilities in accessing essential social services.